2021
DOI: 10.7150/thno.48389
|View full text |Cite
|
Sign up to set email alerts
|

Hsa_circ_0030042 regulates abnormal autophagy and protects atherosclerotic plaque stability by targeting eIF4A3

Abstract: Rationale: Abnormal autophagic death of endothelial cells is detrimental to plaque structure as endothelial loss promotes lesional thrombosis. As emerging functional biomarkers, circular RNAs (circRNAs) are involved in various diseases, including cardiovascular. This study is aimed to determine the role of hsa_circ_0030042 in abnormal endothelial cell autophagy and plaque stability. Methods: circRNA sequencing and quantitative polymerase chain reaction were performed to detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(45 citation statements)
references
References 36 publications
1
44
0
Order By: Relevance
“…Currently most reports are that they act as miRNA sponges to regulate gene expression. 23–27 For example, circSHKBP1 suppresses gastric cancer progression through serving as the sponge of oncogenic miR-582-3p to suppresses HSP90 degradation. 28 Circ-AASDH acts as a sponge for miR-140-3p regulates LUAD cells by inhibiting the proliferation and migration].…”
Section: Discussionmentioning
confidence: 99%
“…Currently most reports are that they act as miRNA sponges to regulate gene expression. 23–27 For example, circSHKBP1 suppresses gastric cancer progression through serving as the sponge of oncogenic miR-582-3p to suppresses HSP90 degradation. 28 Circ-AASDH acts as a sponge for miR-140-3p regulates LUAD cells by inhibiting the proliferation and migration].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research showed that circSEMA5A increased the expression of host gene SEMA5A by recruiting EIF4A3 to enhance mRNA stability of SEMA5A, and thereby promoted BC angiogenesis [ 43 ]. Additionally, hsa_circ_0030042 promoted the cytoplasmic localization of EIF4A3 and inhibits FOXO1 and beclin1 expression by obstructing the interaction between EIF4A3 and their mRNAs [ 44 ]. Emerging studies have demonstrated that through direct interaction, circRNAs can modulate the nuclear localization of proteins as well as their corresponding biological functions.…”
Section: Discussionmentioning
confidence: 99%
“…CircRNAs play key roles in the progression of AS, especially in the function of endothelium vein cells. Hsa_circ_0030042 regulates autophagy and protects atherosclerotic plaque stability by targeting eIF4A3 [ 20 ]. The circular RNA circ_0003204 inhibits the proliferation, migration and tube formation of endothelial cells in atherosclerosis via the miR-370-3p/TGFβR2/phosph-SMAD3 axis [ 21 ].…”
Section: Discussionmentioning
confidence: 99%